Control of floating offshore wind turbines: Reduced-order modeling and real-time implementation for wind tunnel tests - Fontanella, Alessandro; Bayati, Ilmas; Belloli, Marco (Volume 10: Ocean Renewable Energy, 2018)
The present work deals with the implementation of a variable-speed variable-pitch control strategy on a wind turbine scale model for hybrid/HIL wind tunnel tests on floating offshore wind turbines. The effects that scaling issues, due to low- Reynolds aerodynamics and rotor structural properties, have in combination with the HIL technique developed by the authors are studied through a dedicated reduced-order linear coupled model. The model is used to tune the original pitch controller gains so to be able to reproduce the system response of the full-scale floating wind turbine during HIL tests.